-6+2m(m+2)=5(5-5m)

Simple and best practice solution for -6+2m(m+2)=5(5-5m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6+2m(m+2)=5(5-5m) equation:


Simplifying
-6 + 2m(m + 2) = 5(5 + -5m)

Reorder the terms:
-6 + 2m(2 + m) = 5(5 + -5m)
-6 + (2 * 2m + m * 2m) = 5(5 + -5m)
-6 + (4m + 2m2) = 5(5 + -5m)
-6 + 4m + 2m2 = (5 * 5 + -5m * 5)
-6 + 4m + 2m2 = (25 + -25m)

Solving
-6 + 4m + 2m2 = 25 + -25m

Solving for variable 'm'.

Reorder the terms:
-6 + -25 + 4m + 25m + 2m2 = 25 + -25m + -25 + 25m

Combine like terms: -6 + -25 = -31
-31 + 4m + 25m + 2m2 = 25 + -25m + -25 + 25m

Combine like terms: 4m + 25m = 29m
-31 + 29m + 2m2 = 25 + -25m + -25 + 25m

Reorder the terms:
-31 + 29m + 2m2 = 25 + -25 + -25m + 25m

Combine like terms: 25 + -25 = 0
-31 + 29m + 2m2 = 0 + -25m + 25m
-31 + 29m + 2m2 = -25m + 25m

Combine like terms: -25m + 25m = 0
-31 + 29m + 2m2 = 0

Factor a trinomial.
(-31 + -2m)(1 + -1m) = 0

Subproblem 1

Set the factor '(-31 + -2m)' equal to zero and attempt to solve: Simplifying -31 + -2m = 0 Solving -31 + -2m = 0 Move all terms containing m to the left, all other terms to the right. Add '31' to each side of the equation. -31 + 31 + -2m = 0 + 31 Combine like terms: -31 + 31 = 0 0 + -2m = 0 + 31 -2m = 0 + 31 Combine like terms: 0 + 31 = 31 -2m = 31 Divide each side by '-2'. m = -15.5 Simplifying m = -15.5

Subproblem 2

Set the factor '(1 + -1m)' equal to zero and attempt to solve: Simplifying 1 + -1m = 0 Solving 1 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1m = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1m = 0 + -1 -1m = 0 + -1 Combine like terms: 0 + -1 = -1 -1m = -1 Divide each side by '-1'. m = 1 Simplifying m = 1

Solution

m = {-15.5, 1}

See similar equations:

| 8x^2+17x-13=23-6x | | =2-3x+4*2+5*3 | | =2-3*1+4*2+5*3 | | 4x=-16(2)+4 | | 0.04x+0.07(9000-x)=540 | | -6-5x=4 | | -6+n=15 | | 2x+6-3=12-4x+3 | | 6=6x-10 | | 15x+6y=35 | | 16x^2-22x=37 | | 3x^2-8x=24 | | 4x+81=x+81 | | 3x^2-5x-6=a | | =75+6*1000 | | -15+8x-3x=7+4x+55 | | 1000=75+6x | | 15x+6y= | | 3xsquared+5x-6=a | | 90/105 | | -12v+19=0 | | -9(-9-p)=12 | | 3(m-z)+5-(2m-z)= | | 3-4x=11+3x-2 | | Y/13=3/17 | | 900=75+6x | | 100=75+6x | | =75+6*12.5 | | y=-25x^3+75x^2+4x-12 | | =75+6x | | .7+x=.20(7+x) | | 1.2+x=.6(4+x) |

Equations solver categories